Peningkatan Hasil Belajar Materi Penjumlahan Pecahan dengan Pendekatan Konstruktivisme - Rohman, Taufiqur; Ekasari, Paramita Ayu (Mitra PGMI: Jurnal Kependidikan MI, 2021)
The study aimed to answer how the Constructivism approach can improve students' learning outcomes of adding fraction material in fourth-grade students of Madrasah Ibtidayah Tukangan, Ampel District, Boyolali Regency, Academic Year 2015/2016. This Classroom Action Research was carried out in two cycles. Each cycle has four stages, namely planning, implementing, observing, and reflecting. The data collection methods used were post-test observation sheets and documentation. The findings of this study revealed that the implementation of the Constructivism Approach can improve students' mathematics learning outcomes in adding fractions. This increase occurred from the first, and second cycles with the results of the Pre-test and Post-test have increased. In the first cycle, the mean score of the pre-test was 61.67, while the post-test was 68.88. In the second cycle, the mean score of the pre-test was 75, and the post-test was 88.89. Therefore, the mean score of pre-test, and post-test was increased by 13.89 or 22.23%. The increase of the mean score on the Pre-test and Post-test showed that the Constructivism approach can improve student learning outcomes.